Synthesis of marigold-like ZnIn2S4 microspheres at low-temperature. (2022) - Chand, Mool; Rawat, A.S.; Khanuja, Manika; Rawat, Seema; Ranwa, Mitesh
Highlights: Low-Temperature and Template-Free Synthesis of marigold-like ZnIn2 S4 Microspheres. Characterization of the synthesized marigold-like ZnIn2 S4 Microspheres powder with XRD, FESEM, UV–vis. Spectroscopy and XPS. The band gap of ZnIn2 S4 (2.31 eV) is in the visible range, making it perfect for semiconductor applications. Abstract: In this paper, Zinc Indium Sulphide (ZnIn2 S4 ) marigold like Microsphere are synthesized at 80 °C in aqueous solution by using Zinc sulphate ZnSO4, Indium sulphate In2 (SO4 )3 and Thioacetamide C2 H5 NS (TTA). We have characterized the nanopowder of the zinc Indium sulphide, by using various techniques, like UV–Vis spectrophotometer, Field emission scanning electron microscopy (FSEM), X-ray diffraction (XRD) and X-ray photoelectron spectroscopy (XPS). The variation of optical properties in Zinc Indium sulphide by using UV–visible spectroscopy, to find the energy band gap (2.31 eV). The hexagonal phase was confirmed from the X-ray diffraction pattern of ZnIn2S4. We have used a simple route to synthesize the Zinc Indium Sulphide, which involves, no templates, no organic solvents or surfactants, and at low temperature (80 °C). Our synthesized Zinc Indium Sulphide have got promising applications in a wide range of areas like solar energy conversion, electrical nanodevices, photocatalysis, optical devices, and electrical devices, etc.